Science and technology of cuprate-based high temperature superconductor thin films, heterostructures and superlattices — the first 30 years (Review Article) - Habermeier, H.-U. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
During the three decades after the discovery of superconductivity at high temperatures in copper oxides, intense research activities generated a tremendous progress in both, mastering the scientific challenges underpinning the understanding of the properties of these chemically and structurally complex materials as well as achieving a mature technology in preparing single phase bulk specimens — including single crystals — and epitaxially grown single crystalline thin films. This review covers in addition to more basic physics oriented developments mainly technological aspects of complex oxide thin film deposition as an enabling technology to explore the physics of these materials. It consists of two parts: after a brief introduction to the materials development prior to the discovery of superconducting copper oxides, a description of the relevant properties of copper oxide superconductors with focus on YBa2Cu3O7–δ is given, followed by the coverage of essentials of complex oxide thin film deposition technology with the copper oxides at its core. Here, the major physical vapor deposition technologies (evaporation and oxide molecular beam technology, sputtering and pulsed laser deposition) are described followed by an overview of substrate requirements to deposit high quality thin films. Opportunities by choosing special substrates with unique properties far beyond the usual mechanical support for a film are introduced with examples aside from usual lattice mismatch induced strain effects. One is the continuous modification of the strain state by poling ferroelectric oxide substrates linked to a piezoelectric effect, the other is the nanoscale tailoring of substrate step-and-terrace structures resulting in a controllable generation of planar defects in complex oxides, thus contributing to the physics of flux-line pinning in cuprate superconductors. In the second part of this review, first some highlights of single layer thin film research are given such as to tailor thin film orientation, generating well defined antiphase boundaries in YBa2Cu3O7–δ thin films as flux-line pinning centers as well as contributions to understand fluctuation conductivity in relation to the pseudogap state. In the last section new developments in high Tc cuprate based heterostructures and superlattices are reviewed with a special focus on the opportunities offered by interface-induced electronic interactions.